2016
DOI: 10.1021/acscatal.6b01879
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Mechanism of Aqueous CO2 Reduction on Post-Transition-Metal Electrodes using ATR-IR Spectroelectrochemistry

Abstract: The role of metastable surface oxides in the reduction of CO 2 on lead, bismuth, tin, and indium electrodes was probed using in situ attenuated total reflectance infrared (ATR-IR) spectroelectrochemistry. The effect of the surface oxide on the Faradaic efficiency of CO 2 reduction to formic acid was studied by etching and anodizing the electrodes, and the results were correlated with respect to the observed spectroscopic behavior of the catalysts. A metastable oxide is observed on lead, tin, and indium cathode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
182
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 193 publications
(187 citation statements)
references
References 37 publications
4
182
1
Order By: Relevance
“…It was proposed that the formation of this surface‐bound tin carbonate was the key step in electrochemical CO 2 RR to formate because these IR bands were absent on etched Sn that was measured to have a poor electrocatalytic activity (Figure c). The same authors later reported a similar observation about In that its oxide/hydroxide persisted during CO 2 RR and actively participated in the reaction . By contrast, even though Pb supported a metastable oxide under CO 2 RR, this oxide did not play a direct role in the formate production.…”
Section: Mechanistic Studies Using In Situ Characterization Techniquesmentioning
confidence: 62%
“…It was proposed that the formation of this surface‐bound tin carbonate was the key step in electrochemical CO 2 RR to formate because these IR bands were absent on etched Sn that was measured to have a poor electrocatalytic activity (Figure c). The same authors later reported a similar observation about In that its oxide/hydroxide persisted during CO 2 RR and actively participated in the reaction . By contrast, even though Pb supported a metastable oxide under CO 2 RR, this oxide did not play a direct role in the formate production.…”
Section: Mechanistic Studies Using In Situ Characterization Techniquesmentioning
confidence: 62%
“…Recent studies have demonstrated that post‐transition metal oxides have an important impact on the electrochemistry of CO 2 reduction ,,,. This is especially interesting because the Pourbaix diagram for each of the post‐transition metals (except Hg) predicts that there is native oxide present in neutral solutions at 0 V vs. SHE…”
Section: Analysis Of the Performance And Mechanisms Of Oxide‐derived mentioning
confidence: 99%
“…Electrokinetic studies based on Tafel and reaction‐order analyses have proposed possible rate‐determining steps (RDS) for HCOO − formation . Furthermore, in situ IR and Raman analyses have presented direct evidence for intermediates and active sites . Even though intensive efforts have been made in many areas, it is still challenging to fully uncover the reaction mechanism.…”
Section: Introductionmentioning
confidence: 99%